Sektor Unggulan dan Transformasi Ekonomi di Kabupaten Badung - UTAMI, NI MADE LODI DWI; ANTARA, MADE; SURYAWARDANI, I G. A. OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.2, April 2018, 2018)
Leading Sector and Transformation of Economic in Badung Regency The development of tourism in Badung regency is rapidly causing inequality of regional development between north and south and the imbalance of development between economic sectors. The purpose of this study is to analyze the basic sectors and economic structure in Badung Regency. This study uses secondary data in the form of data of Gross Regional Domestic Product (GRDP), growth rate, and data of working population. Data collection methods used were documentation studies and analyzed using location quotient, dynamic location quotient, total shift share, and shift share. The results of analysis showed that the basis sectors in economic structure of Badung Regency is water supply, waste, and recycling sector, construction sector, transportation and warehousing sector, accommodation and feeding supply sector, and information and communications. The agricultural sub-sector has three sub-sub-sectors that are able to become the basis sub-subsector in the future are food crop sub-sub-sectors, horticultural crops sub-subsector, and fishery sub-sector. Two factors causing the change of agriculture, forestry and fishery sub-sector positions in the economic structure of Badung Regency, namely economic structure and location factor. The economic structure of Badung Regency is transformed from agriculture to services, especially tourism services, followed by shifts in labor absorption.